Urban public finance in developing countries - Bahl, Roy W.; Linn, Johannes F. (Oxford [England] ; New York, N.Y. : Published for the World Bank [by] Oxford University Press, 1992)
This book gives policymakers and finance officers at all levels of government in developing countries the tools to loosen constraints on the growth of urban and thus national productivity. As practitioners follow the lessons of comparative experience gathered here, they will begin to mobilize the financial resources to create and sustain livable cities.
Includes bibliographical references (p. 513-539) and index.
rpm 26/08/16
Loans
Keywords: Municipal finance; Local taxation; User charges; Intergovernmental fiscal relations; Developing countries